Law on technology transfer - The National Assembly (2006)
This Law provides for the transfer of technologies in Vietnam, from Vietnam to abroad and from abroad into Vietnam; rights and obligations of organizations and individuals engaged in technology transfer activities; competence of state management agencies; and measures to encourage and promote technology transfer.